GENDER DIFFERENCE AND JOB SATISFACTION: A STUDY AMONG FACULTIES OF PRIVATE COLLEGES IN INDIA - Krishna, G. Suresh (PEOPLE: International Journal of Social Sciences, 2015)
Teaching is one of the most important profession in which the faculties play a major role in improving the standard of an organization and the country. It is important to determine which factors influence the faculties in their job and it’s important to determine their level of job satisfaction. This study examined the influence of gender on job satisfaction among faculties of private colleges and investigated the extent to which faculties differ in various attitudes and attributes, level of satisfaction with the type of work they do. Stratified random samples of 215 academic faculties from private colleges in India were selected for this study. Findings indicate that differences between male and female faculties in the level of satisfaction were due to negative work experiences such as castism, favoritism, physical appearance, gender discrimination and due to certain source of stress from major life changes, unforeseen events and family social isolation. These negative experiences generated lower levels of job satisfaction among men than women and all these factors that might explain different job satisfaction among faculties at private colleges in India. The attributes that stood out as significant are namely: technical support at work, understanding teaching and research process and responsibilities, broadening role, belonging to an ageing group, need for more outcomes of the work. The paper recognizes the importance of gender differences in workplace and it should be controlled to improve the job satisfaction among faculties in private colleges.